The missing ethical dimension: an application of TCE to the case of the Inquiry Committee into Oil-for-Food Program Scandal - Da Veiga, M. R.; Major, M. (AAAJ Special Forum Workshop, 2017)
Purpose: This paper seeks to address decisions of governance oversight structures in the context of systemic failures of probity / ethics, applying Williamson’s (1999) framework to explore “probity” and “independence” transactions’ attributes enhanced with the “virtues ethics” of McCloskey’s (2006) framework. Design/methodology/approach: Through historical narrative case based research and built on the case of the 2004 United Nations inquiry of the scandal of fraud and corruption in the management of the Oil-for-Food Programme (OFFP) for Iraq the investigation seeks to respond to the research questions: i) has the inquiry worked?; and ii) did the TCE’s discriminating alignment hypothesis succeed in the case of the Oil-for-Food scandal inquiry? Findings: The paper demonstrates that the inquiry into the OFFP, which contains “sovereign” as well as “quasi-judiciary” transactions elements did not work. The Transaction Cost Economics (TCE) alignment hypothesis did not function and “probity” hazards – “ethics” – cannot be relieved by governance structures, i.e., incentives. Originality/value: We argue that TCE should be modified to include McCloskey’s “virtues ethics” behavioural dimension as a transaction costs’ reduction device and an explanatory framework for bureaucratic ethical failures.